Cul3-KLHL20 ubiquitin ligase: physiological functions, stress responses, and disease implications. Issue 1 (March 2016) - Chen, Hsin-Yi; Liu, Chin-Chih; Chen, Ruey-Hwa
Abstract Cullin-RING ubiquitin ligases are the largest Ubiquitin ligase family in eukaryotes and are multi-protein complexes. In these complexes, the Cullin protein serves as a scaffold to connect two functional modules of the ligases, the catalytic subunit and substrate-binding subunit. KLHL20 is a substrate-binding subunit of Cullin3 (Cul3) ubiquitin ligase. Recent studies have identified a number of substrates of KLHL20-based ubiquitin ligase. Through ubiquitination of these substrates, KLHL20 elicits diverse cellular functions, some of which are associated with human diseases. Furthermore, the functions, subcellular localizations, and expression of KLHL20 are regulated by several physiological and stressed signals, which allow KLHL20 to preferentially act on certain substrates to response to these signals. Here, we provide a summary of the functions and regulations of KLHL20 in several physiological processes and stress responses and its disease implications.